A Case of Severe Acute Kidney Injury Exacerbated by Canagliflozin in a Patient with Type 2 Diabetes. (4th June 2019) - Hassani-Ardakania, Kimya; Lipman, Mark L.; Laporta, Denny; Yu, Oriana Hoi Yun
Abstract : Background. Sodium glucose cotransport (SGLT)-2 inhibitors are the newest class of antihyperglycemic agents used as second- or third-line treatment in the management of type 2 diabetes. Although the use of SGLT-2 inhibitors has not been shown to cause nephrotoxicity, there have been case reports of SGLT-2 inhibitor use being associated with acute kidney injury. Case Presentation. A 72-year-old woman with a history of type 2 diabetes and no known chronic renal insufficiency presented to the emergency room with a 3-day history of nausea, vomiting, and increased somnolence. She was found to have potassium level of 7.4 (normal: 3.5-5.5) mmol/L and a markedly elevated creatinine level at 1154 (normal: 45-95) μ mol/L. Imaging of the abdomen and pelvis did not reveal any findings of obstruction. Urine microscopy showed many granular casts. In the absence of other causes for her clinical presentation, the patient was diagnosed with acute kidney injury secondary to ischemic acute tubular necrosis, with canagliflozin use likely an important contributing factor. Conclusions. Physicians should inform patients to stop the use of SGLT-2 inhibitors when patients are unable to maintain hydration or during acute illness. Use of SGLT-2 inhibitors in managing type 2 diabetes should be done with caution among more vulnerable populations, including individuals with cognitive impairment and the elderly.